Carbon Emission Disclosure by Non-Financial Companies in Indonesia: A Perspective of Stakeholder Theory - Widarjo, Wahyu; Sudaryono, Eko Arief; Kurniawati, Estetika Mutiaranisa; Putra, Adhitya Agri; Wibawa, Baskara Agung (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2024)
This study aims to examine the determinant factors of carbon emission disclosure in the perspective of stakeholder theory. Stakeholder theory is the most often use as literature in the carbon emission research. Most studies only capture the carbon emission disclosure based on stakeholder theory elements of economic performance and stakeholder power. This study examines comprehensively the perspective of stakeholder theory by considering economic performance, stakeholder power, and strategy posture. Research sample includes 67 non-financial companies listed on the Indonesian Stock Exchange 2017-2020. Data are accessed from annual report and sustainability report. Economic performance is measured by return on assets and return on equity. Stakeholder power is measured by managerial ownership and leverage. Strategy posture is measured by ISO certification and environmental costs. The result shows that stakeholder power (proxied by leverage) and strategy posture (proxied by ISO certification) have effects on carbon emission disclosure.